PENGARUH ETIKA PROFESI TERHADAP KOMITMEN PROFESI PADA DOSEN PTS DI SEMARANG - Wartini, Sri (PRESTASI, 2011)
The purposes of the research were to test the available influences of professional ethics towards professional commitments and to test the biggest influence of professional ethics dimension towards professional commitments.Â  Dimension of professional ethics studied here were responsibility, justice, autonomy, and high moral integrity. The Samples were consisted of 150 lectures of management from Private University in Semarang. Research method used was survey method using questionnaires. Hypothesis test used double regression. The result of the research found that there were some influences of professional ethics towards professional commitments in lectures from State University. The other result test performed to compare beta coefficient value, it showed that dimension of beta coefficient of responsibility was the biggest one if it is compared with other beta coefficients. It means that responsibility dimension had biggest influence towards professional commitments lectures from State University in Semarang. Keywords: professional ethics, professional commitments